A copula-based assessment of renewable energy droughts across Europe. (December 2022) - Otero, Noelia; Martius, Olivia; Allen, Sam; Bloomfield, Hannah; Schaefli, Bettina
Abstract: Meeting carbon-reduction targets will require thorough consideration of climate variability and climate change due to the increasing share of climate-sensitive renewable energy sources (RES). One of the main concerns arises from situations of low renewable production and high demand, which can hinder the power system. We analysed energy droughts, defined as periods of low energy production (wind plus solar generation) or high residual load (demand minus production), in terms of two main properties: duration and severity. We estimated the joint return periods associated with energy droughts of residual load and power production. We showed that moderate winter energy droughts of both low renewable production and high residual load occur every half a year, while summer events occur every 3.6 and 2.4 years (on average). As expected, the occurrence of energy droughts tends to decrease with the degree of the severity of the energy drought, and moderate and extreme energy droughts showed longer return periods for most countries. In general, we found a large variability across Europe in summer, with some countries (e.g. Italy) being more sensitive to energy droughts. Our results highlight the relevance of sharing RES during prolonged periods of low production and high demand. Highlights: European countries are frequently exposed to moderate winter energy droughts. Copulas model the dependence between the duration and the severity of energy droughts. Energy droughts are more frequent and longer lasting in winter than in summer. Joint return periods increase with the degree of the severity of the energy droughts.